PENDIDIKAN ISLAM MODERAT DALAM MENUMBUHKAN KARAKTER RELIGIUS DAN KEBANGSAAN DI SEKOLAH MENENGAH PERTAMA - Ulfa, Fahrunisa Miladia; Farih, Muhammad (Jurnal Al-Fatih, 2025)
This study aims to explore the application of moderate Islamic education in the learning process of Islamic Religious Education (PAI) at SMP Negeri 17 Gresik, as well as its contribution to the formation of students' religious and nationalism characters. The method used was a qualitative approach with a case study type, where data were collected through interviews, observations, and documentation involving the principal, teaching staff, and a number of students. Data analysis was conducted using the Miles and Huberman technique. The results showed that the application of the principles of religious moderation in Islamic education learning plays a major role in enriching the study of Islamic education development, especially in strengthening the value of moderation at the secondary education level. This study specifically presents empirical evidence related to the implementation of religious moderation values in SMP Negeri 17 Gresik, which can be used as a reference for other educational institutions to integrate these values into their curriculum and teaching and learning process. In addition, this study offers a critical evaluation of the practice of moderate Islamic education, which is useful for consideration in developing more effective teaching strategies by educators and policy makers. The implementation of religious moderation values is proven to have a positive influence on the formation of students' religious character and nationalism, by encouraging attitudes of tolerance, openness, and respect for diversity. In conclusion, the internalization of moderation values not only strengthens an inclusive and rahmatan lil 'alamin religious foundation, but also fosters a sense of patriotism, social responsibility, and national spirit in students. This finding is very relevant in strengthening the character of the Indonesian nation in the midst of ethnic, cultural and religious diversity.